Evaluasi Kinerja Pompa Sentrifugal P.100/03 Berdasarkan Head Losses dan Deviasi terhadap Kondisi Desain - Moh Solikhul Umam; Hisyam Ma’mun; Aan Burhanuddin (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2026)
Pumping systems play a pivotal role in crude oil distribution; however, performance studies are often conducted in laboratory settings that often fail to represent actual field operations. This study evaluates the performance of the P.100/03 centrifugal pump in the crude oil distribution system at PPSDM Migas Cepu by comparing actual conditions with design specifications, using head-loss analysis. The methodology employs field studies integrated with technical calculations utilizing operational data, including suction and discharge pressures, flow rates, fluid characteristics, and piping configurations. Key analyzed parameters encompass head losses, total pump head, hydraulic power, and pump efficiency. The results demonstrate a total pump head of 56.78 m. A significant finding reveals a drastic efficiency decline from 60.28% under design conditions to 23.1% in actual operation. This performance degradation is attributed to pump operation deviating from the Best Efficiency Point (BEP), substantial head losses within the piping system, and early indications of cavitation on the suction side. This research underscores that actual operational conditions significantly influence pump performance, necessitating regular evaluations and maintenance to optimize the efficiency of field pumping systems.